The Perlocutionary Effect of Teachers’ Oral Corrective Feedback in Multigenerational EFL Classroom - Aswati, Dewi; Shalihah, Andi Musfiqah; Amin, Fatimah Hidayahni; Sakkir, Geminastiti (Journal for Teaching and Education for Scholars, 2025)
This study investigated the emotional responses of EFL learners from different generational cohorts- Generation Z, Millenial, and Generation X- toward oral corrective feedback (OFC) provided by a Millennial lecturer in an online classroom.  Rooted in speech act theory, particularly the concept of perlocutionary acts, the research explores how teachers’ feedback is emotionally received, interpreted, and responded to by learners of varying age groups. A qualitative approach was employed, involving observation of a Zoom-based English class and in-depth semi-structured interviews with nine selected students representing the three generations. Data were analyzed thematically using Miles and Huberman’s framework. The findings reveal five primary emotional responses to OFC: anxiety, embarrassment,  motivation, appreciation, and discomfort. While Generation Z expressed higher sensitivity and nervousness, especially in response to public or explicit correction, millennials generally viewed direct feedback as constructive. Generation X preferred reflective feedback forms such as elicitation. These varied emotional reactions demonstrate that the perlocutionary effects of OFC differ based on generational identity, learner preferences, and the classroom setting. This study highlights the importance of generation-aware and emotionally responsive feedback practices in EFL instruction, particularly in online learning environments with limited non-verbal communication. It contributes to the affective dimension of corrective feedback research by emphasizing how feedback not only corrects linguistic errors but also impacts learner emotion, engagement, and motivation.